Muhammadiyah Di Kota Makassar 1985-2015 (Kajian Tentang Pendidikan Dasar Dan Menengah) - Rahayu, Sry (Universitas Negeri Makassar, 2018)
The study aims at discovering the existence of Muhammadiyah in Makassar in 1985 - 2015, understanding the role of Muhammadiyah in Makassar in managing the education, and analyzing the influence of Muhammadiyah on the people in Makassar in education field. The study employed descriptive analytic approach by providing specific description on the profile of Muhammadiyah in Makassar, the way Muhammadiyah in managing education, and its influence on the people in Makassar. The techniques of writing and data gathering employed history method conducted in four stages, namely heuristic (data gathering), critique (data analysis), interpretation (data interpretation), historigraphy (writing the data into a whole event). The results of the study reveal that the establishment of Muhammadiyah in Makassar was pioneered by Al-Yamani. Al-Yamani was well known as a Batik seller from Surabaya, who opened the store in Straat market, now as Nusantara Street in Makassar. In the field of education, Muhammadiyah had given numerous contribution by building many madrasah and pesantren (Islamic schools) with the concept of teaching of Islamic and general science curriculum. The educational institution established by Muhammadiyah was managed in the form of a business charity with the organizer formed an assembly with the name of Assembly of Primary and Secondary Education with the existence of schools of Muhammadiyah with the foundation of Islam based on Al Qur'an and Hadith. Based on the aforementioned foundation, it will form a Muslim with noble characters, competen, confident, and useful for the people.